Fracture Analysis for the Triple Junction of Bekhair- Brifca- Zawita, Anticline Northern Iraq - Shakir Al-Kubaisi, Manal; Mohammed Shakir, Madeha (Iraqi Journal of Science, 2023)
The aim of the research is to detect the relation between the fracture sets and systems with the stages of folding. The triple junction area of the research comprises the three faced plunges of three anticlines Bekhair, Brifca and Zawita anticline. GEOreint, ver 9.5.0 was used for analyzing and classifying the data collected from the field measurements on 11 stations in proportion to the orthogonal tectonic axes. The age of exposed rocks ranges from Paleocene up to Miocene. The fractures were represented as joints, veins in addition to different types of faults. The Kinematic analysis of the fractures revealed that the stress caused the (ac) and (hko> a) fractures is coincides with the regional compression stress that form the folds where the max. Principle stress (σ1) is oriented NE-SW parallel to the tectonic axis (a) that lead to shorten the layers in perpendicular direction to the fold axis. While the extension stress was determined in the form of (hko> b) where the (σ1) oriented horizontally in NW-SE direction parallel to the tectonic axis (b) and coincides with the regional extension stress. High distribution of (hkl) in different directions during fracturing and faulting indicates the local stresses associated with more than one phase of deformation.